Primary lipoblastic nerve sheath tumor in an inguinal lymph node mimicking metastatic tumor: a case report and literature review - Chen, Chengxin; Cao, Jiachen; Song, Lingxie; Wang, Wenjie; Guo, Dandan; Shi, Qi; Zhang, Ying; Chen, Yunzhao; Liu, Chunxia; Li, Feng (Frontiers in Oncology, 2023)
Lipoblastic nerve sheath tumors of soft tissue are characterized as schwannoma tumors that exhibit adipose tissue and lipoblast-like cells with signet-ring morphology. They have been documented to arise in various anatomic locations, including the thigh, groin, shoulder, and retroperitoneum. However, to our knowledge, this tumor has not been previously reported as a lymph node primary. We present herein the first case of a benign primary lipoblastic nerve sheath tumor arising in an inguinal lymph node in a 69-year-old man. Microscopic examination revealed a multinodular tumor comprising fascicles of spindle cells, as well as adipocytic and lipoblast-like signet-ring cell component in the context of schwannoma. Despite the presence of some bizarre cells with nuclear atypia, no obvious mitotic activity or necrosis was observed. Immunohistochemical analysis showed strong and diffuse expression of S-100, SOX10, CD56, and NSE in the spindle cells as well as in the signet-ring lipoblastlike cells and the mature adipocytes. Sequencing analysis of the neoplasm identified six nonsynonymous single nucleotide variant genes, specifically NF1, BRAF, ECE1, AMPD3, CRYAB, and NPHS1, as well as four nonsense mutation genes including MRE11A, CEP290, OTOA, and ALOXE3. The patient remained alive and well with no evidence of recurrence over a period of ten-year followup.